Applied anatomy of female pelvic plexus for nerve-sparing radical hysterectomy(NSRH) - Fan Ye; Hongyu Su; Hang Xiong; Wenxin Luo; ZiHeng Huang; Guoqing Chen; Hongying Zhou (BMC, 2023)
Abstract Background Nerve-sparing radical hysterectomy(NSRH)has the advantage of reducing postoperative complications and improving postoperative quality of life. The separation and protection of the pelvic plexus in NSRH is extremely important and challenging. Methods 24 female cadaveric hemipelves were dissected. Morphologic patterns and compositions of pelvic plexus as well as relationship of pelvic plexus to the surrounding structures were observed and documented. Results Two patterns of superior hypogastric plexus were observed, including fenestrated and cord-like shape. The origin of bilateral hypogastric nerves were inferiorly to upper margin of promontory about 1.6 ± 0.1 cm and parallel to the ureter in front of the sacrum. Pelvic splanchnic nerves(PSN)from the second sacral nerve, the third sacral nerve and the forth sacral nerve were observed combing with the hypogastric nerves within the lateral rectal ligament. The sacral sympathetic trunk can be identified anteriorly or medially to the anterior sacral foramen. We identified the boundaries of pelvic plexus as following: the upper margin is formed by the PSNs from the third sacral nerve, posterior margin by inferior rectal artery, and anteriorly by vesical venous plexus. The uterine branches from pelvic plexus were observed accompanying with uterine artery, while other branches were inferiorly to the artery. The PSNs were located beneath the deep uterine veins within the cardinal ligament. The upper margin of pelvic plexus was observed directly approach to urinary bladder within the vesico-vaginal ligament as a single trunk accompanying with ureter, between the middle and inferior vesical veins. Conclusions Our study clarified the intricate arrangement, distribution and relationship of female pelvic plexus and the related structures to provide reference index for NSRH application. The innervation patterns of bladder and uterine were clarified, and by tracing these visceral branches of pelvic plexus, we suggest several new important land markers for NSRH.